Development of Punch and Kick Counting Equipment in Taekwondo Using FSR Sensors - Namyee, Chai; Nuangmeuy, Aukkarapon; Yaibuates, Mayoon (Journal of Engineering and Industrial Technology, Kalasin University, 2024)
This research aims to develop a device for counting the number of punches and kicks performed by Taekwondo athletes using an Arduino Uno R3 board combined with FSR sensor technology. The purpose is to use it for practicing speed skills in Taekwondo competitions. The utilization of sensor technology in counting instances helps alleviate issues arising from human error. The development of such equipment is crucial for preparing and enhancing the skills of athletes in Taekwondo. Experimental results involving punching and kicking methods, conducted in 10 sets of 20 counts each, revealed that the developed prototype device demonstrated an accuracy rate of 94% for punch counts and 91% for kick counts.